2018
DOI: 10.1021/acs.jpcc.8b08148
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Direction Dependence of Thermodynamic Stability of Ferroelectric BiAlO3(0001) Polar Surfaces

Abstract: Polar surfaces of ferroelectric oxides are of great importance for both fundamental and practical interest. In this report, we present a theoretical study to determine the thermodynamic stability and electronic properties of ferroelectric BiAlO3(0001) surfaces. According to the calculated surface phase diagram, we predict that the equilibrium stoichiometries are distinct for the oppositely polarized BiAlO3 surfaces under the same chemical conditions. In addition to nonstoichiometry of the surface chemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…This is due to the characteristics of metastability of the polarization-reversed BAO(0001) surface terminations relative to the thermodynamically preferred polarization-unreversed BAO Z+ and Z− surface terminations. 22 More interestingly, different from the so-called polarization compensation mechanism of ferroelectric BAO(0001) substrates, 4,13,43,48 an unusual charge transfer opposite the polarization compensation can be seen in the MoS 2 overlayer of the MoS 2 /BAO Z− heterostructure, as shown in Figure 5. In other words, the MoS 2 overlayer on the down-polarized (Z−) ferroelectric BAO(0001) surface is electrostatically n-doped.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…This is due to the characteristics of metastability of the polarization-reversed BAO(0001) surface terminations relative to the thermodynamically preferred polarization-unreversed BAO Z+ and Z− surface terminations. 22 More interestingly, different from the so-called polarization compensation mechanism of ferroelectric BAO(0001) substrates, 4,13,43,48 an unusual charge transfer opposite the polarization compensation can be seen in the MoS 2 overlayer of the MoS 2 /BAO Z− heterostructure, as shown in Figure 5. In other words, the MoS 2 overlayer on the down-polarized (Z−) ferroelectric BAO(0001) surface is electrostatically n-doped.…”
Section: Resultsmentioning
confidence: 94%
“…It can be observed that after full structure relaxation, the BAO Z+ substrate is still terminated with the −Al−O 3 −Bi atomic layer (as shown in Figure 2a), which is the same as the initial thermodynamically preferred BAO Z+ surface termination without MoS 2 adsorption. 22,25 Such information indicates that the adsorption of MoS 2 has no significant influence on the atomic structures of the BAO Z+ surface. Similar conclusions can also be obtained for the relaxed MoS 2 /BAO Z+↓ heterostructure (as shown in Figure 2b).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations